Expert Wakaf, Wakif Family Social Security in The Achievment of Sustainable Development Goals - Mulya Syamsul, E; Kuswaya, Adang (Journal of International Conference Proceedings, 2023)
This study's overarching goal is to examine family social security as the tool for the primary goal of expert waqf, and specifically to examine how it applies to wakif families in a way that is consistent with the Sustainable Development Goals (SDGs). The instrument of expert waqf is a model offered by Islam for the continuity of an established and prosperous family as the aim of waqf in Islam. This research method uses a descriptive qualitative and analysis obtained from the literature review approach of several articles or research, the results of this study are that waqf is an Islamic instrument for presenting welfare based on the usefulness of assets those held or handed over for social purposes, expert waqf is a model of waqf that is recognized besides khoiri waqf, expert waqf focuses on the value of benefits in the wakif family as the scholars have formulated it, in the SDGs achievements it was found that expert waqf provides guarantees for the sustainability of social, economic stability , Education and others as SDGs achievement indicators in education, economic sustainability and avoiding poverty. While the conclusion from this study, that expert waqf provides social security for wakif families in various fields, both education, economics, social, all of which are in line with the achievements of the SDGs by fulfilling strategic indicators, so that the resilience of the wakif family is guaranteed and the continuity of a decent life in the future can be achieved